Toxicidade aguda e atividade antinociceptiva do óleo essencial do Ocimum basilicum L. (MANJERICÃO), em Mus musculus (camundongos) - Venâncio, Antonio Medeiros (2006)
The aim of this study was to determine the acute toxicity and the antinociceptive action, of the Essential Oil obtained from leaves of Ocimum basilicum L. (LAMIACEAE), PI-197442, manjericão maria bonita . The Ocimum presents various species, used in the folk medicine, like antispasmodic, sedative and carminative, in agriculture as repellent of insects. The acute toxicity was determined by probit method using 5 groups (N=6) of mice, both genders. The LD50 was 0,532g/kg from the animals. The antinociceptive effect was studied by three models of nociception: The abdominal writhes induced by acetic acid 0,6% (i.p.), Hot Plate and the Test of Formalin. The OE increased the nociceptive effect dependent-dose in the concentrations 50, 100 and 200mg/kg in 48,02%, 64,48% and 77,49%, respectively, in the Test of Wrighting. In the Hot Plate, the OE increased the time of staying under the thermal stimulus in the times of 0, 15, 30 and 60 minutes. In the time of 15 min, was obtained the most significant effect. The morphine 10mg/kg was used as antinociception pattern. The antagonist Nalaxone opiod, reverted the effect of OE-50 in all tested times. In the Test of Formalin, the OE presented significant effect just in the second phase. The OE-200, in this phase, reduced the licking times of hind paw in 74,66%. These results showed that the OE of Ocimum basilicum L. presented high toxicity (i.p.) and showed peripherical and central antinociception activities.